A Keynesian approach to modeling the long-term interest rate - Tanweer Akram (Levy Economics Institute of Bard College, 2021)
There are several widely used benchmark models of the long-term interest rate in quantitative finance. However, these models have yet to incorporate Keynes's valuable insights about interest rate dynamics. The Keynesian approach to interest rate dynamics can be readily incorporated in the benchmark models of the long-term interest rate. This paper modifies several benchmark interest rate models. In these modified models the long-term interest rate is related to the shortterm interest rate and a Wiener process. The Keynesian approach to interest rate dynamics can be useful in addressing theoretical and policy issues.
Keywords: E12; E43; E50; E58; E60; G10; G12; G41; 330; Long-Term Interest Rate; Bond Yields; Monetary Policy; Short-Term Interest Rate; John Maynard Keynes